2019
DOI: 10.3389/fgene.2019.00605
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Germline Mutations in SEMA5A Associated With Infantile Spasms

Abstract: Infantile spasm (IS) is an early-onset epileptic encephalopathy that usually presents with hypsarrhythmia on an electroencephalogram with developmental impairment or regression. In this study, whole-exome sequencing was performed to detect potential pathogenic de novo mutations, and finally we identified a novel damaging de novo mutation in SEMA5A and a compound heterozygous mutation in CLTCL1 in three sporadic trios wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…Previous studies showed that Sema5a was associated with autism spectrum disorder and mental health development disorders [37]. We also found Ppp1r9a targeted by lncRNAs Gm15521 and Gm13974; Sema5a targeted by lncRNA 4933406K04Rik.…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies showed that Sema5a was associated with autism spectrum disorder and mental health development disorders [37]. We also found Ppp1r9a targeted by lncRNAs Gm15521 and Gm13974; Sema5a targeted by lncRNA 4933406K04Rik.…”
Section: Discussionsupporting
confidence: 67%
“…Classical transcriptome analysis indicates that some transcripts, including the gene, are downregulated in some individuals with autism [25]. This deleted region includes the gene and some other genes, with studies associating it with causing infantile epilepsy [29,30]. Importantly, the respective mutations of Arg-676 and Ser-951 of Sema5A are critically associated with ASD and/or ID, probably depending on individual patients [27,28], suggesting that Sema5A is actually the responsible gene product of ASD and/or ID.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses using genetically modified mice have demonstrated that Sema5A is involved in connections between different neurons in certain brain regions [31,32]. Herein, we report that neurite-like process elongation induced by the ASD-and ID-associated Arg676-to-Cys (R676C) mutation [30] within the TSP domain of Sema5A is mediated by a signalosome, including Rac1 guanine-nucleotide exchange factor (GEF) Dock5 as the Rac1 activator, in the N1E-115 cell line [33][34][35][36]. This provides evidence for a unique group of molecules involved in potential therapeutic target pathways in Sema5A-related ASD at the molecular and cellular experimental levels.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…None of the genes in the 18 genomic regions that were significantly associated with intestinal atresia in the Holstein‐Friesian population have been previously implicated in this phenotype, although USH2A has been associated with microtia‐atresia in humans (Wang, Wang, et al, 2019). Several genes have been associated with other congenital defects in humans (Delmaghani & El‐Amraoui, 2022; Fedick et al, 2015; Jaworek et al, 2013; Mégarbané et al, 2016; Pfendner & Lucky, 1993; Wang, Liu, et al, 2019; Zhang et al, 2016). Interestingly, several of these defects relate to ciliopathies.…”
Section: Discussionmentioning
confidence: 99%